Green UMKM : Transformasi Bisnis dalam Upaya Menjaga Kelestarian Lingkungan - Herlina Ilyas; Erty Rospyana Rufaida; Sasliana Sasliana; Sari Fatimah Mus (Owner : Riset dan Jurnal Akuntansi, 2025)
A green future refers to a collective vision and effort to create a living environment that is healthier, more sustainable and in balance with nature. Green MSMEs is an initiative that supports small businesses so they can run their businesses with attention to environmental impacts. This research aims to review the production of copra and coconut charcoal towards environmental risk management through the implementation of environmentally friendly and green-minded principles. This research uses a qualitative case study method including interviews, participant observation and documentation on MSMEs in Katumbangan Village. The results of this research show that Copra and Coconut Charcoal MSMEs have positive and negative impacts on the surrounding community. The positive impact is that it can create new jobs so that it can improve people's standard of living, and the negative impact is the high level of environmental pollution produced, such as coconut water waste, the aroma of sulfur used to make white copra which causes a distinctive aroma and air pollution from the charcoal burning process. which uses simple methods so it does not consider aspects that cause environmental pollution. So it is necessary to transform MSMEs into green MSMEs by applying indicators from the aspects of production (input, energy sources and waste processing), marketing (products, prices and promotions), human resources (motivation and training) and finance (investment, environmental costs and reporting). finance) so that the role of MSMEs can achieve the agenda of sustainable development goals or what are known as Sustainable Development Goals